2020
DOI: 10.1101/2020.01.09.899922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fundamental resource specialization of herbivorous butterflies decreases toward lower latitudes

Abstract: Revealing drivers of variation in resource specialization is a long-standing goal in ecological and evolutionary research. As a general prediction, the degree of resource specialization increases towards lower latitudes. Although herbivorous insects are one of the best-studied consumer groups, factors determining the degree of specialization on large spatial scales are poorly understood. Herein, we focused on the fundamental host breadth of 246 herbivorous butterfly species distributed across the Japanese arch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Enquist et al (2019) indicated that climatic EH is the main driver of the global tree species abundance distribution, and more climatically stable regions have harbored rare species. The variation in resource specialization can shape the distribution pattern of terrestrial biodiversity for ground beetles, and climatic change can regulate the host breadth and morphology of ground beetles (Settele et al, 2012; Turlure et al, 2010; Nakadai et al, 2020). Thus, climatic EH could regulate terrestrial biodiversity, particularly for trees and ground beetles, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Enquist et al (2019) indicated that climatic EH is the main driver of the global tree species abundance distribution, and more climatically stable regions have harbored rare species. The variation in resource specialization can shape the distribution pattern of terrestrial biodiversity for ground beetles, and climatic change can regulate the host breadth and morphology of ground beetles (Settele et al, 2012; Turlure et al, 2010; Nakadai et al, 2020). Thus, climatic EH could regulate terrestrial biodiversity, particularly for trees and ground beetles, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Forewing length can be regarded as an indicator of body size, which may constraint physiological parameters, such as resource exploitation and requirement (Hashimoto & Ohgushi, 2017), tolerance to environmental stresses (Clissold & Simpson, 2015), and dispersal ability (Chai & Srygley, 1990). Specifically, if researchers combined the information of this data paper with monitoring and census datasets including butterfly as a targeted taxa (e.g., the censuses of the National Survey of the Natural Environment and the Monitoring Sites 1,000 Project by the Ministry of the Environment in Japan), this data would provide opportunities to test biodiversity patterns across time and space (e.g., Nakadai et al, 2018;Nakadai, Nyman, Hashimoto, Iwasaki, & Valtonen, 2020). For example, the impact of climate change on geographical and phenological patterns of butterfly body size at the community-level can be tested.…”
Section: Introductionmentioning
confidence: 99%